A Study of Emotional Maturity and Academic Achievement among Higher Secondary Students in Chennai District - Priya, G Menaka; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education; Vol 7 No 1 (2022): Journal of Advanced Research in English and Education, 2022)
Emotional maturity is a state of balanced feeling and self-control. Emotional maturity is the ability to bear tension and to develop high tolerance for the circumstaces that we disagree. When we face a complex situation, our level of emotional maturity is one of the biggest factors in determining our ability to cope up with them. Adolescence is a transitional stage of physical and mental human development that involves biological (i.e., pubertal), social and psychological changes. Education is the process of development from child to Adolescence or adulthood. The school education particularly higher Secondary School education plays an important role in personal and professional success. But during this stage of life many factors influence, the process of education an especially academic accomplishment that is why the present study has been conducted to investigate the relationship of emotional maturity and the academic achievement among Higher Secondary students. How to cite this article: Priya GM, Selvakumar YS. A Study of Emotional Maturity and Academic Achievement among Higher Secondary Students in Chennai District J Adv Res Eng & Edu 2022; 7(1): 4-7. DOI: https://doi.org/10.24321/2456.4370.202211